2020
DOI: 10.1016/j.scitotenv.2020.139904
|View full text |Cite
|
Sign up to set email alerts
|

Decadal shifts in soil pH and organic matter differ between land uses in contrasting regions in China

Abstract: Soil organic matter (SOM) and pH are critical soil properties strongly linked to carbon storage, nutrient cycling and crop productivity. Land use is known to have a dominant impact on these key soil properties, but we often lack the ability to examine temporal trajectories across extensive spatial scales.Large-scale monitoring programmes provide the data to evaluate these longer-term changes, and under different climatic conditions. This study used data from Chinese soil surveys to examine changes in soil pH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Specifically, both SOM and TN were significantly negatively correlated with pH, indicating that lower pH within a certain range leads to higher SOM and TN contents, resulting in higher yield. This is consistent with the findings of Sun Yiming [33], who studied the variations in soil pH and SOM content under different land uses (dry fields, paddy fields, grasslands, forests, and unused land) over a period of 20 years and observed a sharp decrease in soil pH in northern China and a slight decrease in southern China over this period, with both regions experiencing a notable increase in SOM content. Zainal [34] indicated that applying liquid organic fertilizer to sweetcorn leads to a linear increase in the SOM and TN content, which is consistent with the findings of this study.…”
Section: Interactions Between Soil Physiochemical Properties and The ...supporting
confidence: 91%
“…Specifically, both SOM and TN were significantly negatively correlated with pH, indicating that lower pH within a certain range leads to higher SOM and TN contents, resulting in higher yield. This is consistent with the findings of Sun Yiming [33], who studied the variations in soil pH and SOM content under different land uses (dry fields, paddy fields, grasslands, forests, and unused land) over a period of 20 years and observed a sharp decrease in soil pH in northern China and a slight decrease in southern China over this period, with both regions experiencing a notable increase in SOM content. Zainal [34] indicated that applying liquid organic fertilizer to sweetcorn leads to a linear increase in the SOM and TN content, which is consistent with the findings of this study.…”
Section: Interactions Between Soil Physiochemical Properties and The ...supporting
confidence: 91%
“…This might be due to the strong nitrification process in the aerobic environment during the wheat cropping season in which more H + was generated to counteract the increase in pH from paddy rice season. SOC is critical for soil structure and workability, the ability of soils to store nutrients and water, and for the global C cycle (Sun et al, 2020). In this study, almost all treatments significantly enhanced the SOC, which was dominated by the retention of straw residues (Y.…”
Section: Effects Of Crop Rotation and Fertilization On The Changes In...mentioning
confidence: 77%
“…Soil pH plays an important role in crop production, nutrient chemistry, soil organisms, and shaping plant community composition (Sun et al, 2020). Both CU and BBU fertilizations resulted in a significant shortterm increase in soil pH under RG and RR rotations (Figs.…”
Section: Effects Of Crop Rotation and Fertilization On The Changes In...mentioning
confidence: 99%
“…In summary, values range as follows: soil pH, 7.20-7.59; SOM, 1.78-91.4 g/kg; CEC, 1.31-12.6 cmol/kg; mean particle size, 11.18-115 μm; weight specific surface area, 48.7-296 m 2 /g; conductivity, 45.3-251 μs/cm. The key variables soil pH and SOM are broadly typical for soils from northeast China (Sun et al, 2020;Zhang, 2011). The total concentrations of the major elements Al, Fe and Mn, which can influence the chemistry of Pb, were ~18,000-55,000 mg/kg, ~37,000-130,000 mg/kg and ~690-4,000 mg/kg, respectively.…”
Section: Properties Of the Soils Used In The Studymentioning
confidence: 99%